2021
DOI: 10.3889/oamjms.2021.6006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of Kinect Motion Sensing Input Device’s 3D Models: A Comparison to Direct Anthropometry and 2D Photogrammetry

Abstract: AIM: This study aims to evaluate the accuracy and reliability of Kinect motion sensing input device’s three-dimensional (3D) models by comparing it with direct anthropometry and digital 2D photogrammetry. MATERIALS AND METHODS: Six profiles and four frontal parameters were directly measured on the faces of 80 participants. The same measurements were repeated using two-dimensional (2D) photogrammetry and (3D) images obtained from Kinect device. Another observer made the same measurements for 30% of the images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Among the 29 studies included in the systematic review, different study groups were identified: the most common control group was direct anthropometry. Among the studied groups, static-stereophotogrammetry was the most represented with 14 study groups [9,10,19,[23][24][25][26]29,31,36,38,43]; eight studies investigated infrared structured light [9,12,35,38,39,[42][43][44][45]; six studies considered portable-stereophotogrammetry [32][33][34][39][40][41] and structured light [9,20,28,30,37,38], while laser scanners [18,21,22,27,40] were investigated in five groups. Only one study reported the use of LED structured light [9].…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 29 studies included in the systematic review, different study groups were identified: the most common control group was direct anthropometry. Among the studied groups, static-stereophotogrammetry was the most represented with 14 study groups [9,10,19,[23][24][25][26]29,31,36,38,43]; eight studies investigated infrared structured light [9,12,35,38,39,[42][43][44][45]; six studies considered portable-stereophotogrammetry [32][33][34][39][40][41] and structured light [9,20,28,30,37,38], while laser scanners [18,21,22,27,40] were investigated in five groups. Only one study reported the use of LED structured light [9].…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…The measurement technique and number and type of landmarks used for the assessment were collected. Seventeen studies [12,[18][19][20][22][23][24][25][26][27][28]31,32,[36][37][38][39] investigated only linear measures using a range of 6-48 landmarks, four studies [21,40,43,44] investigated both linear and angular measures, and four [34,42,45] investi-gated both linear measures and surface-to-surface deviation. Three types of measurements were employed in two articles [29,33], and two [9,30] additionally investigated surface-to-surface deviation only.…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 3 more Smart Citations